1998
DOI: 10.1088/0953-4075/31/18/020
|View full text |Cite
|
Sign up to set email alerts
|

High-order harmonic generation at long range in intense laser pulses

Abstract: The physics of high-order harmonic generation in single-electron molecular ions at long range (large internuclear distances) is examined by exact numerical solutions of the three-dimensional time-dependent Schrödinger equation. These numerical solutions show that photon energies can be produced with energies exceeding the atomic cut-off law I p +3U p , where I p is the ionization energy and U p is the ponderomotive energy. It is shown that preferential high-order harmonic generation occurs at critical distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Quasistatic tunneling ionization models of single-electron atoms predict E max =10U p [20,34]. In the case of extended molecules, we have shown previously that collisions with neighboring ions can raise this up to 12U p , thus extending highorder harmonic generation plateaus beyond the atomic maximum E max = I p + 3.17U p [36]. This has been confirmed in simulations of chains of atoms [29].…”
Section: Resultssupporting
confidence: 65%
“…Quasistatic tunneling ionization models of single-electron atoms predict E max =10U p [20,34]. In the case of extended molecules, we have shown previously that collisions with neighboring ions can raise this up to 12U p , thus extending highorder harmonic generation plateaus beyond the atomic maximum E max = I p + 3.17U p [36]. This has been confirmed in simulations of chains of atoms [29].…”
Section: Resultssupporting
confidence: 65%
“…We have shown that collision of ionized electrons with neighboring ions in molecules can lead to even larger harmonic orders with photon energies of 6U p up to 12U p , thus extending the recollision energy, cut-off law (1) [24].…”
Section: Introductionmentioning
confidence: 89%
“…The source of asec radiation is HOHG by recollision of the ionized electron with its parent [23] or neighboring ions [24]. Unfortunately, the efficiency of such spectra is low, as illustrated in Figure 1.…”
Section: Attosecond Pulse Synthesismentioning
confidence: 99%
“…The HHG pro- * m.vafaee@modares.ac.ir cess in molecules is more complex than that in atoms because of nuclear motion [12], two-center interference [13] and different orientations of molecule with respect to the laser field [13]. Effects of different initial vibrational states [14,15], initial nuclear velocities [16] and relation between electronic wavepacket expansion and internuclear distance on the HHG produced by H + 2 [17] have been reported. In addition, extraction of nuclear dynamics from HHG spectra [18], effect of nuclear motion on the HHG efficiency by varying pump-probe time delay [19], on the broadening of cutoff regime [20], on the length of generated attosecond laser pulses [21] and on the generation of isolated attosencond laser pulses for H + 2 have been investigated [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In most theoretical works mentioned above, electron and nuclei are considered quantum mechanically in a one-dimensional (1D) model. The fulldimensional electron wavepacket expansion during laser interaction and its consequent HHG cannot be described properly by a one dimensional model [17].…”
Section: Introductionmentioning
confidence: 99%